Neuropathology: Foundations in Diagnostic Pathology - Prayson Richard A ([?] Elsevier, 2012)
Part of the "Foundations in Diagnostic Pathology" series, this title provides information on neoplastic and non-neoplastic conditions of the central and peripheral nervous systems. It offers guidance on the evaluation and diagnosis of a broad spectrum of neuropathic entities using morphologic, immunohistochemical, and molecular genetic techniques